Deficiência visual e matemática: análise das práticas educativas para uma vida independente na educação infantil - Mendes, Jammes Ferreira (2012)
The central object of this study are the ADL / Pevi consisting of care specific to children with visual impairments. These services are characterized by activities related to routine as getting dressed, eating, move through space independently, using the bathroom, among others, which are intended to provide the child with visual impairments the opportunity to acquire habits self-sufficiency in order to become autonomous individuals and active in the social environment in which they live. Calling attention to the pedagogical nature of the activities in ADL, such assistance has to be thought of as not only training but also as an important tool which facilitates learning, which can lead to children with visual impairments to develop comprehensive. For this pedagogical character is that today we call Pevi. The present study aims at investigating the role of Educational Practices for Independent Living (Pevi) for the approach of mathematical content in the educational process of children with visual impairments. Therefore, we performed a qualitative study, based on the study of the relationship between Pevi, formerly known as Activities of Daily Living (ADL) and the possible mathematical content covered during treatment in early childhood education. To understand this relationship, the theoretical frameworks used were Arruda (2001) and Bruno (1997), in light of cognitive development theory of Piaget. We began this investigation with the study on Pevi in order to describe their main activities and procedures necessary to perform them. Next, we conducted a preliminary analysis of the mathematical content that can be addressed through the completion of these activities step by step, along with a pilot study, which consisted of comments in the kindergarten room and living room of the ADLs of the Institute of the Blind Fortaleza. A preliminary analysis of possible Pevi think that the next stage was the intervention of the researcher with the subjects of research in carrying out their activities. The intervention performed with the subjects in this study suggest the understanding of mathematical ideas they discussed were showing, and at the end of the study, noted an advance in this understanding by analyzing the speech and actions of individuals. This makes the pedagogical nature of Pevi is highlighted and becomes part of the education of children with visual impairments.